SCF(FBXO22) targets HDM2 for degradation and modulates breast cancer cell invasion and metastasis - Bai, Jin (Proc Natl Acad Sci U S A, 2019)
Human homolog of mouse double minute 2 (HDM2) is an oncogene frequently overexpressed in cancers with poor prognosis, but mechanisms of controlling its abundance remain elusive. In an unbiased biochemical search, we discovered Skp1-Cullin 1-FBXO22-ROC1 (SCF(FBXO22)) as the most dominating HDM2 E3 ubiquitin ligase from human proteome. The results of protein decay rate analysis, ubiquitination, siRNA-mediated silencing, and coimmunoprecipitation experiments support a hypothesis that FBXO22 targets cellular HDM2 for ubiquitin-dependent degradation. In human breast cancer cells, FBXO22 knockdown (KD) increased cell invasiveness, which was driven by elevated levels of HDM2. Moreover, mouse 4T1 breast tumor model studies revealed that FBXO22 KD led to a significant increase of breast tumor cell metastasis to the lung. Finally, low FBXO22 expression is correlated with worse survival and high HDM2 expression in human breast cancer. Altogether, these findings suggest that SCF(FBXO22) targets HDM2 for degradation and possesses inhibitory effects against breast cancer tumor cell invasion and metastasis.